Flow calibration of the Bryan Canal radial gate at the United Irrigation District - Bonaiti, Gabriele, author; Leigh, Eric, author; Karimov, Askar, author; Fipps, Guy, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
In an effort to improve the management of the Bryan Canal, the United Irrigation District in South Texas installed a radial gate in place of a pre-existing vertical slide gate structure with the objectives of establishing telemetry and remote control capabilities, and providing the District the ability to control the gates based on flow. This paper discusses the calibration of the radial gate for flow based on the head differential and gate opening. Details are provided on the equipment and instrumentation used, which included pressure transducers for upstream and downstream water levels, gate opening sensor, and doppler and velocity flow meters. The calibration of the doppler flow meter will be discussed along with the methods used to determine actual radial gate opening from sensor data and the problems caused by hysteresis. Flow rate was calculated from the head differential across the gate and gate opening using a submerged orifice equation. By adjusting the discharge coefficient, the equation was calibrated in such a way that total calculated flow matched the total measured flow. The flow data was further analyzed for individual flow events. Data was collected continuously over three months. This paper discusses the process of analyzing data and determining the conditions for which the equation is valid.
Meeting irrigation demands in a water-challenged environment
Presented at Meeting irrigation demands in a water-challenged environment: SCADA and technology: tools to improve production: a USCID water management conference held on September 28 - October 1, 2010 in Fort Collins, Colorado.